2020
DOI: 10.1785/0120190117
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Rupture Dimensions of Three Major Earthquakes in Sichuan, China, for Early Warning and Rapid Loss Estimates

Abstract: Large earthquakes, such as Wenchuan in 2008, Mw 7.9, Sichuan, China, provide an opportunity for earthquake early warning (EEW), as many heavily shaken areas are far (∼50  km) from the epicenter and warning times could be sufficient (≥5  s) to take preventive action. On the other hand, earthquakes with magnitudes larger than ∼M 6.5 are challenging for EEW because source dimensions need to be defined to adequately estimate shaking. Finite-fault rupture detector (FinDer) is an approach to identify fault rupture e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 64 publications
0
15
1
Order By: Relevance
“…The FinDer line-source model characterizes the entire fault rupture including those segments with no surface exposure. Compared with the results of Li et al (2020a), who tested FinDer with a larger trigger threshold (20 cm/s 2 ), the length of the line-source model is underestimated by about 50 km (corresponding to 0.1 magnitude units). This difference is caused by sparse station density around the Wenchuan earthquake as discussed in Li et al (2020b).…”
Section: Finder Trigger Thresholdscontrasting
confidence: 59%
See 4 more Smart Citations
“…The FinDer line-source model characterizes the entire fault rupture including those segments with no surface exposure. Compared with the results of Li et al (2020a), who tested FinDer with a larger trigger threshold (20 cm/s 2 ), the length of the line-source model is underestimated by about 50 km (corresponding to 0.1 magnitude units). This difference is caused by sparse station density around the Wenchuan earthquake as discussed in Li et al (2020b).…”
Section: Finder Trigger Thresholdscontrasting
confidence: 59%
“…In most installations, FinDer adopts the GMPEs developed by Cua and Heaton (2009) that were derived from strong-motion records in California (M 2-M 7.3) and the Next Generation Attenuation (NGA) strong-motion dataset (M 2-M 8). Real-time and offline tests of FinDer in the U.S. West Coast, Switzerland, Italy, Japan, and China (Böse et al, 2012(Böse et al, , 2015(Böse et al, , 2018Li et al, 2020a) have confirmed that the templates are globally applicable to crustal earthquakes. In previous work (Li et al, 2020a), we compared the GMPE of Cua and Heaton (2009) with the regional relationship used in the fifth-generation hazard zoning map in southwestern China, as well as with PGA values, that were observed during the 2008 M S 8.0 Wenchuan, 2013 M S 7.0 Lushan and 2017 M S 7.0 Jiuzhaigou earthquakes.…”
Section: Ground-motion Prediction Equationsmentioning
confidence: 81%
See 3 more Smart Citations